Sintesis Membran Ultrafiltrasi Selulosa Asetat Untuk Pengolahan Limbah Cair Mall: Variasi Waktu Penguapan - Liona Margarita Siahaan; Jhon Armedi Pinem; Idral Amri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Membrane is a thin layer, a barrier between two phases that are semipermeable, and serves as a selective separation media. In this research, membrane was prepared from cellulose acetate by phase inversion method. The purpose of this research was to determine the effect of solvent evaporation time to the performance of membranes asymmetry in the production of membranes for waste water treatment mall. Membrane prepared with variation of solvent evaporation time of 25, 45 and 65 seconds and operating pressure of 1, 3 and 5 bars. Characterization of the membrane is covering flux, rejection, SEM (Scanning Electron Microscopy), FTIR (Fourier Transform Infrared) and tensile strength. The results of SEM analysis showed all the membranes that are formed has an asymmetric structure. The results of FTIR analysis showed the absence of acetone solvent, acid formic and MSG in membrane. This research produed porous membrane and it had asymmetric structure.Key words : asymmetric membrane, mall, ultrafiltration and evaporation time